MODERN ECONOMIC EVALUATION OF DEVELOPMENT OF ENTREPRENEURSHIP IN THE REPUBLIC OF KAZAKHSTAN - A.N.Nurzhanova; M.O. Ryspekova (Academic Journal of Physical and Chemical Sciences, 2019)
The article considers the current state of Kazakhstani business from a legal point of view, i.e. what features are typical for small, medium and large businesses. The study made an in-depth analysis of their main indicators, such as: the number of registered, active, by the dimension of enterprises of various forms of ownership, the output of products in small and medium businesses, in terms of financial and economic activities of medium and large enterprises; the number of people employed in small and medium businesses in organizational form. In addition, the article made a SWOT analysis of the activities of entrepreneurship in Kazakhstan.